Pathological Role of Natural Killer Cells in Parkinson's Disease: A Systematic Review - Zhang, Le; Zhang, Yingshuang; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2022)
Parkinson's disease (PD) is one of the common neurodegenerative diseases that is characterized by selective degeneration of dopaminergic neurons in the substantia nigra, and misfolding of α-synuclein into aggregates is thought to contribute to its pathology. Studies have shown that immune-inflammatory responses are involved in the development of PD and play an important role in α-synuclein scavenge. Natural killer (NK) cells are first responders in immune cells and can directly promote immune defense mechanisms by cytotoxicity and by secreting cytokines. Recent discoveries suggest that NK cells are increasingly recognized in the pathological features of PD. However, the mechanisms underlying it have not been fully understood. In this review, we systematically retrieved and evaluated published evidence about the functions of NK cells in PD. We find alterations in the number of NK cells and cytotoxicity during the progression of PD, and it seems that NK cells play a neuroprotective role in PD pathogenesis, which may further reveal novel targets for the management and treatment of PD.